ELECTRICAL RESISTIVITY AND CHARACTERIZATION OF INDIUM DOPED ZINC OXIDE COATED KENAF FIBER - Sani, N.A.; Manaf, M.E.A.; Ahsan, Q.; Osman, E.; Doan, V.A. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Research on conductive coating on natural or plant fibers has gained attention due to arising drive for green technology in electronic and electrical industry. This study aims to investigate the effects of alkaline treatment (2%, 4%, 6% and 8%) and indium doping concentration (In/Zn: 5%, 7%, 9% and 11%) on the surface resistivity and characteristics of indium doped zinc oxide (IZO) coated kenaf fiber. The process starts with chemical treatment of kenaf fiber by sodium hydroxide (NaOH). Then, the treated fibers are immersed in indium doped zinc oxide sol gel and annealed in a furnace. The final samples are characterized using FTIR and SEM-EDX, while the surface resistivity is measured by using Monroe portable resistivity meter. The results show that the alkaline treatment promotes good interfacial bonding between kenaf and IZO coating as demonstrated by smooth coating and low surface resistivity with the best result was obtained using 8% of NaOH concentration. This finding can be attributed mainly to the elimination of impurities, wax, lignin and hemicellulose, of which could act as interface barrier. The doping of indium on ZnO contributes to a significant decrease of surface resistivity of IZO coated kenaf. The resistivity is decreased to the lowest at 9% of indium doping but increases at further addition which is probably due to doping solubility limit.